2023
DOI: 10.1039/d2me00285j
|View full text |Cite
|
Sign up to set email alerts
|

Electron and ion transport in semi-dilute conjugated polyelectrolytes: view from a coarse-grained tight binding model

Abstract: Conjugated polyelectrolytes (CPEs) are a rising class of organic mixed ionic-electronic conductors, with applications in bio-interfacing electronics and energy harvesting and storage devices. Here, we employ a quantum mechanically informed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Future work will focus on bridging the intrachain to interchain gap, which will ultimately need to be addressed by multichain condensed phase simulations. Emerging methods like electronic coarse-graining are likely to be useful here. In this way, computational methods will be able to inform both the design and processing of radical polymers.…”
Section: Polymer Structures and Crest Explorationmentioning
confidence: 99%
“…Future work will focus on bridging the intrachain to interchain gap, which will ultimately need to be addressed by multichain condensed phase simulations. Emerging methods like electronic coarse-graining are likely to be useful here. In this way, computational methods will be able to inform both the design and processing of radical polymers.…”
Section: Polymer Structures and Crest Explorationmentioning
confidence: 99%
“…The existence of anisotropic models for molecular and polymeric systems are well-known and could be adapted to improve chemical fidelity at reduced computational cost. 29,67,68 IV. CONCLUSION We have developed a simple but powerful approach to describing doping reaction-induced morphology changes in molecularly doped systems using Reactive MC.…”
Section: Resultsmentioning
confidence: 99%
“…For example, density functional theory (DFT) has been used to extract the relationship between atomistic conformation and electrochemical properties such as electronic coupling , and conductance by modeling charge transport at the quantum level. , These studies show the strong dependence of charge transport properties on local conformations (e.g., bond angles and rotations) but are limited to the number and size of conformations that are observable due to the computational cost required to simulate each chain . Furthermore, DFT cannot predict electrochemical properties on its own but needs to be coupled with other methods to account for longer time and length scales associated with transport. ,, To access higher-length scales (such as those relevant in polymer solutions), it has been shown that it is possible to coarse-grain some of this quantum-level information while retaining the most important features relevant to charge transport such as electronic coupling. , Another way to access longer-length scales is by simulating the charge transport with kinetic Monte Carlo (KMC) models . For example, this method has been used to evaluate the efficiency of charge transport in slurry RFBs, , polymer solar cells, , and polymer field-effect transistors, , but it has only recently been applied to study charge transport in redox-active polymer solutions …”
Section: Introductionmentioning
confidence: 99%
“…25,35,43−45 To access higher-length scales (such as those relevant in polymer solutions), it has been shown that it is possible to coarse-grain some of this quantum-level information while retaining the most important features relevant to charge transport such as electronic coupling. 46,47 Another way to access longer-length scales is by simulating the charge transport with kinetic Monte Carlo (KMC) models. 48 For example, this method has been used to evaluate the efficiency of charge transport in slurry RFBs, 49,50 polymer solar cells, 51,52 and polymer field-effect transistors, 53,54 but it has only recently been applied to study charge transport in redox-active polymer solutions.…”
Section: ■ Introductionmentioning
confidence: 99%